(3efP HOGjI GdbQf GdSGOS hMJi fgGjI GdbQf GdJGSY GdgLQjs - (3QGaJ eMeO eMeO(B, (3GdfHQGhjs ((3GdEScfOQjI(B:s (3ecJHI RgQGA GdTQb(B,s, 2000)
(3JLO aj gPG GdcJGH (B: (3CgejI GdfbhO GdESdGejI ,fbhO Ohd TQb GdYGde GdESdGej ,fbhO Ohd ZQH GdYGde GdESdGej ,fbhO GdeQGHWjf ,GdehMOjf ,Hfj MaU ,fbhO Hfj RjGf , Hfj eQje ,fbhO OhdI Hjf fUQs
(3HjHdjhZQGajG U(B.381s
Keywords: (3GdYGde GdGSdGejs; (3GdfbhOs